Christian Education Based on Digital Technology and Local Wisdom: An Experimental Study Addressing the Vulnerable Generation of Strawberries - Elfin Warnius Waruwu; Rejeki Putra Gulo (Harati: Jurnal Pendidikan Kristen, 2025)
This study examines the didactic reconstruction of Christian Religious Education based on digital technology and local wisdom as an effort to overcome the challenges of the Strawberry Vulnerable Generation. The research uses a qualitative approach with a literature study method. The results of the study show that the Strawberry Generation requires an adaptive, contextual, and transformative model of Christian Religious Education. The integration of digital technology through e-learning platforms, mobile applications, social media, and interactive media has been proven to be able to increase student involvement in the learning process. However, the use of technology needs to be balanced with strengthening local wisdom values such as mutual cooperation, solidarity, respect for the community, and contextual spirituality so that students are not trapped in individualism and instant culture. The didactic reconstruction of Christian Religious Education that was developed emphasizes the synergy between digital innovation and the preservation of local cultural values as the foundation for the formation of resilient Christian character. This research contributes to the development of Christian Religious Education learning models that are relevant to the digital native generation while strengthening faith and cultural identity in the digital era. Thus, Christian Religious Education based on digital technology and local wisdom can be a strategic approach in building a generation that is adaptive, critical, characterful, and resistant to the complexities of modern life.